179k views
17 votes
Combine any like terms in the expression. If there are no like terms, rewrite the expression.

6pg + 5pg - 6pg

2 Answers

9 votes

Answer: 5pg

Explanation:

Like terms are terms that have the same variables and powers. E.g. 8p²g+9p²g=17p²g

8+9=17

8pg+9pg=17pg

8pg²+9pg²=17pg²

How to work out the question:

6pg+5pg=11pg

11pg-6pg=5pg

User Paul Kavanagh
by
5.6k points
4 votes

Answer: I believe the answer is just 5pg?

Step-by-step explanation: Hope this helps but sorry if it's wrong. Not sure if I'm understanding the question correctly.

User Bo Persson
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.